Conversation Analysis and Language Analysis on Selected Episodes of The Big Bang Theory: Stereotypes of Scientists - Raden Roro Rieta Anggraheni (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims at analyzing how the language in the popular sitcom The Big Bang Theory forms stereotypes towards genius scientists and what power relation is constructed. This study used Critical Discourse Analysis (CDA) as the conceptual framework and combined two types of analysis, language analysis and  conversation analysis (CA). Therefore, this study also puts an emphasis on how the analytical framework helps to achieve the objective of CDA. The data are taken from the transcripts of two selected episodes of the Big Bang Theory. The result shows that geniuses are represented as awkward and excessively logical persons who find it difficult to maintain a good social interaction and struggle to develop their social skills. This stereotype shows that the group is minor in the society they live among. Through the female characters in the story, it is also found that women are stereotyped as less logical gender. The female scientist characters are the embodiment of the idea that women are supposed to be caring and affectionate in nature, the qualities a mother has. This issue on gender shows that in the post-modern American society, with the concept of liberalism, stereotypes still exist. It indicates that there is no absolute freedom; power domination manifests in various forms out there.